Avaliação de polpa de cagaita (eugenia dysenterica DC.) submetida ao congelamento e atomização - Santos, Mara Núbia Guimarães dos (2015)
The Brazilian Cerrado presents great diversity of native species, but the form of agricultural expansion has ignored the high potential of this biome. Among the fruits of the Cerrado, has the cagaita (Eugenia dysenterica DC.), with great potential for consumption mainly by the possible uses in culinary. The high perishability of most fruits, combined with seasonality, have driven the development of technological processes, with a view to better use of these fruits, beyond the scope of its postharvest life. Given these factors, this study aimed to evaluate the effect of freezing and atomization on the bioactive compounds of cagaita and evaluate the working life of cagaita atomized pulp stored for 45 days at a temperature of 30 °C. The study was conducted with fruit cagaita collected mature in the morning at the Federal University of Goiás, in Goiânia, GO, to obtain the frozen pulp, and then atomized. The samples were analyzed for content of total phenolics, total flavonoids, tannins, antioxidant potential (for ABTS and DPPH), vitamin C, β-carotene (HPLC), sugars (fructose, glucose, sucrose) (for HPLC), mineral profile, volatile compounds. The results showed influence of conservation methods (freezing and atomization). May be considered that the drying method spray dryer showed better performance when compared to freezing technique cagaita pulp, one time showed higher levels of total phenolics, total flavoinoides and condensed tannins, after drying the pulp, contributing to increase the antioxidant potential (ABTS). However, food preservation methods studied were not effective for the preservation of the vitamin C content of cagaita fresh. The methods of preservation (freezing and spray) showed different levels of sugars (fructose, glucose), but showed no sucrose contents to nennhum method. Using the spray technique, there is the possibility of extracting volatile compounds different in the lowest percentage of area compared with fresh fruit and also the frozen pulp. During the storage time (45 days) at 30 °C was observed the increase of the maintainer and bioactive compounds present in the pulp atomized cagaita, indicating that the atomization may be a technique for preserving fruit. The work contributed to a greater appreciation and enjoyment of the Brazilian Cerrado and at the same time, encouraging the preservation of this biome